TO THE PROBLEM OF THE OLIGOCENE-MIOCENE BOUNDARY POSITION IN THE NORTHERN CAUCASUS (IN SUPPORT OF THE CAUCASIAN REGIONAL STAGE) - Beluzhenko E.V.; Kovalenko E.I. (My University, 2006)
Stratigraphic position of the Oligocene-Miocene (Paleogene-Neogene) boundary in the northern Caucasus and, in this connection, of the Alkun Formation and the Caucasian regional stage in geological sections of Maikop deposits, primarily in those of the Belaya and Kuban rivers, is considered. Arguments in support of the Caucasian regional stage are presented and necessity of distinguishing the Karadzhalganian regional stage is called in question. Stratigraphic implications of the Alkun Formation, the regional reference horizon traceable in many sections of the northern Caucasus, are discussed. It is substantiated based on nannoplankton, dinocysts, foraminifers, and distinctive lithological features of deposits that the Oligocene-Miocene boundary is confined to the Alkun Formation at the Belaya River. © MAIK "Nauka/Interperiodica" 2006.
Keywords: ALKUN FORMATION; CAUCASIAN REGIONAL STAGE; DINOCYSTS; FORAMINIFERS; MAIKOP DEPOSITS; NANNOPLANKTON; NORTHERN CAUCASUS; OLIGOCENE-MIOCENE BOUNDARY; Кайнозой::Неоген::Миоцен; Кайнозой::Палеоген::Олигоцен; Cenozoic::Neogene::Miocene; Cenozoic::Paleogene::Oligocene